Acceptance of Low Vision Aids in Patients of ARMD, Myopic Degeneration and Diabetic Retinopathy - Shilpa Singh; Charu Mithal; Sandeep Mithal (Delhi Journal of Ophthalmology)
Purpose: To compare and correlate the differences in acceptance of Low vision Aids in patients of ARMD, Myopic degeneration and Diabetic Retinopathy. Materials and Methods: Low Vision Aids were prescribed to each of the 15 patients in each group of Diabetic Retinopathy, Age Related Macular Degeneration and Myopic Degeneration with vision less that 6/18 in the better eye, with irreversible damage and their acceptance in each group was observed. Results: In patients of ARMD the mean scores pre LVA and post LVA were 25.33 and 32.47 and after applying Paired t test (two tailed t test) and taking P value as < .05 as statistically significant. And a p value <0.01 was found and this was considered to be statistically significant. In patients of Myopic degeneration the mean scores pre LVA and post LVA were 26.00 and 37.27 and after applying Paired t test (two tailed t test) and taking P value as < .05 as statistically significant. And a p value <0.001 was found and this was considered to be extremely statistically significant. In patients of DM the mean scores pre LVA and post LVA were 22.87 and 27.27 and after applying Paired t test (two tailed t test) and taking P value as < .05 as statistically significant. And a p value <0.2 was found and this was considered to be not statistically significant. Conclusions: Statistical methods concluded that low vision aids were of benefit in patients of Age Related Macular Degeneration and Myopic Degeneration, while they showed no benefit in patients of Diabetic Retinopathy.